Collaborative conservation in action: a real-time Colorado case study - Erdmann, Dieter, author; Palmer, Carl, author (Colorado State University. Libraries, 2009)
Colorado Open Lands, Park County, and Beartooth Capital (a private investment fund) have been collaborating to conserve and restore top priority conservation properties in South Park for the past several years, building on the more than 10-year track record of partnership between Park County and Colorado Open Lands. Beartooth Capital is a private investment fund dedicated to making investments that conserve important ranches while generating returns for investors, and its involvement is enabling the partnership to extend its reach and achieve conservation goals that had been thought out of reach. In this session, Dieter Erdmann, Director of Conservation Operations for Colorado Open Lands, and Carl Palmer, co-founder of Beartooth Capital, will introduce their organizations and each party's role in the partnership, exploring the details, strengths and challenges to this kind of innovative approach to landscape-scale conservation.
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. Carl Palmer is co-founder of Beartooth Capital Partners. Dieter Erdmann is Director of Conservation Operations for Colorado Open Lands.
Keywords: South Park; Tarryall Creek Ranch; Park County; Colorado Open Lands; Beartooth Capital; landscape-scale conservation